2020
DOI: 10.3390/antibiotics10010003
|View full text |Cite
|
Sign up to set email alerts
|

Biofilms as Promoters of Bacterial Antibiotic Resistance and Tolerance

Abstract: Multidrug resistant bacteria are a global threat for human and animal health. However, they are only part of the problem of antibiotic failure. Another bacterial strategy that contributes to their capacity to withstand antimicrobials is the formation of biofilms. Biofilms are associations of microorganisms embedded a self-produced extracellular matrix. They create particular environments that confer bacterial tolerance and resistance to antibiotics by different mechanisms that depend upon factors such as biofi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
208
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 271 publications
(257 citation statements)
references
References 319 publications
(296 reference statements)
1
208
0
2
Order By: Relevance
“…Biofilm formation is a common mechanism that promotes the survival and persistence of medically important bacteria in different abiotic and biotic niches. Approximately 80% of chronic and recurrent bacterial infections in humans are related to biofilms, some of which associated with high mortality and morbidity ( Banerjee et al, 2020 ; Uruén et al, 2020 ). Biofilms are defined as a community of sessile microbes held together by a secreted matrix of polysaccharides, proteins, and extracellular DNA, adherent to a surface, interface, or other cells.…”
Section: Introductionmentioning
confidence: 99%
“…Biofilm formation is a common mechanism that promotes the survival and persistence of medically important bacteria in different abiotic and biotic niches. Approximately 80% of chronic and recurrent bacterial infections in humans are related to biofilms, some of which associated with high mortality and morbidity ( Banerjee et al, 2020 ; Uruén et al, 2020 ). Biofilms are defined as a community of sessile microbes held together by a secreted matrix of polysaccharides, proteins, and extracellular DNA, adherent to a surface, interface, or other cells.…”
Section: Introductionmentioning
confidence: 99%
“…In our results, the growth rates, biofilm formation, and bacterial viability were significantly inhibited by overexpressing antisense yycF in the ASyycF ATCC29213 and ASyycF MRSA strains (Figures 2 and 3A,B). Biofilms are constructed with microorganisms embedded in a self-produced extracellular matrix [21]. As shown in the SEM observations, biofilm accumulation was obviously decreased in antisense yycF-overexpressing strains, which indicated that antisense yycF could negatively regulate biofilm metabolism (Figure 2C).…”
Section: Discussionmentioning
confidence: 90%
“…As shown in the SEM observations, biofilm accumulation was obviously decreased in antisense yycF-overexpressing strains, which indicated that antisense yycF could negatively regulate biofilm metabolism (Figure 2C). Indeed, biofilms are usually supposed to decrease the sensitivity of biofilm cells to various antimicrobial agents up to 1000-fold when compared with their planktonic forms [10,21,22]. Vancomycin, as the "gold standard" of treatment, has been applied clinically for serious MRSA infections [23].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The P. aeruginosa ctpA mutant was also reported to attach robustly to glass surfaces [ 10 ]. eDNA, which is an essential constituent of biofilms, is secreted through active secretion or cell lysis [ 29 ]. Autolysis-dependent eDNA release has been shown to promote biofilm formation in several bacterial species [ 30 , 31 , 32 ].…”
Section: Introductionmentioning
confidence: 99%